2016
DOI: 10.1097/mib.0000000000000798
|View full text |Cite
|
Sign up to set email alerts
|

Dairy Products, Dietary Calcium, and Risk of Inflammatory Bowel Disease

Abstract: Milk consumption may be associated with a decreased risk of developing CD, although a clear dose-response relationship was not established. Further studies are warranted to confirm this possible protective effect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
43
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 77 publications
(48 citation statements)
references
References 46 publications
3
43
2
Order By: Relevance
“…Some investigations report that a higher intake of milk is associated with a moderately increased risk of inflammatory bowel disease [44,45], whereas others find an inverse association or none [46][47][48][49][50]. In comparison to individuals that do not consume milk, the European Prospective Investigation into Cancer and Nutrition cohort including 401,326 participants reported that individuals consuming milk had significantly reduced odds of Crohn's disease (OR 0.30, 95% CI: 0.13-0.65) and nonsignificantly reduced odds of UC (OR 0.85, 95% CI: 0.49-1.47) [51]. Notably, pasteurized fresh milk in contrast to fermented milk products such as yoghurt contains bioactive milk exosomes [52].…”
Section: Discussionmentioning
confidence: 99%
“…Some investigations report that a higher intake of milk is associated with a moderately increased risk of inflammatory bowel disease [44,45], whereas others find an inverse association or none [46][47][48][49][50]. In comparison to individuals that do not consume milk, the European Prospective Investigation into Cancer and Nutrition cohort including 401,326 participants reported that individuals consuming milk had significantly reduced odds of Crohn's disease (OR 0.30, 95% CI: 0.13-0.65) and nonsignificantly reduced odds of UC (OR 0.85, 95% CI: 0.49-1.47) [51]. Notably, pasteurized fresh milk in contrast to fermented milk products such as yoghurt contains bioactive milk exosomes [52].…”
Section: Discussionmentioning
confidence: 99%
“…The European Investigation into Cancer and Nutrition study found that individuals that consumed milk had significantly reduced odds of developing CD (OR: 0.30, 95% CI: 0.13–0.65), suggesting a protective effect with dairy product consumption [28]. Individual dairy products consisted of milk, yogurt, and cheese with varying fat content (e.g., full fat, skimmed, semi-skimmed, and unspecified).…”
Section: Diet In the Etiology Of Ibdmentioning
confidence: 99%
“…CIDs are complex diseases with both genetic and environmental factors involved in the disease development. Some genetic and environmental susceptibility factors are shared between the CIDs whereas other factors might differ [4,5,6,7,8,9,10,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25]. CIDs are frequent; IBD affects up to 0.5% of the population in the Western world [26] and RA and PsO have global prevalences of 0.3–1.0% and 1.5%, respectively [27,28].…”
Section: Introductionmentioning
confidence: 99%